Day 1 Tue, August 11, 2020 2020
DOI: 10.2118/203600-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Flow Behaviour and Transport Mechanisms During Low salinity and Protein Enzyme Bio-surfactant EOR Flooding

Abstract: The focal point of this project is to investigate and assess the potentiality of an enhanced waterflooding process by a naturally generated surfactant (Protein-Enzyme bio-surfactant). The effect of low salinity (LSW), and LSW combined with a bio-surfactant (Protein-Enzyme) in a tertiary mode flooding comparatively. A high salinity water (HS) (0.75 M) was used to flood in the secondary mode after aging the crude saturated core with an initial water saturation of 19%, a recovery of 68.15% oil initially in place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, when a calcium ion (Ca 2+ ) is exchanged, a little molecule of thickness of a well-ordered layer of water is adsorbed by the clay. In the case of sodium ion (Na + ), disordered layers of water are adsorbed, leading to an indefinite swelling of the clay [2,25,49]. Fragmentation of smectite or mixed-layer smectite and illite occurs when the clays swell.…”
Section: Key Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when a calcium ion (Ca 2+ ) is exchanged, a little molecule of thickness of a well-ordered layer of water is adsorbed by the clay. In the case of sodium ion (Na + ), disordered layers of water are adsorbed, leading to an indefinite swelling of the clay [2,25,49]. Fragmentation of smectite or mixed-layer smectite and illite occurs when the clays swell.…”
Section: Key Findingsmentioning
confidence: 99%
“…Waterflooding is dominant amongst fluid injection methods and responsible for high levels of oil production (over fifty percent of recovery worldwide) [1][2][3]. This technique is employed to increase hydrocarbon recovery when there is a significant decline in primary production resulting from the depletion of the reservoir pressure [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, enzyme has been proved with its good EOR potential in various reservoirs such as low permeability reservoirs (Liu and Zhang, 2011), conventional reservoirs (Jain and Sharma, 2012), and heavy oil reservoirs (Feng et al, 2009). In addition, enzymes have been tested with good EOR performance under a wide range of formation water salinity (Feng et al, 2007;Morgan et al, 2020a) and reservoir temperature (Feng et al, 2007). Also, it has been found that enzyme could potentially be used as an effective additive for different EOR processes including cold heavy oil production, CSS, waterflooding, and CO2 or nitrogen injection (Ott et al, 2011).…”
Section: Enzyme Applicationsmentioning
confidence: 99%